A study of partnering relationship between shipper and carrier in Singapore : issues, ranking and satisfaction - Ma, Victor Kam Wing (2010)
The project studies the partnering relationship between Shipper and Carrier and finds out the critical success factors of a partnership. The topic of this project primarily focuses on the Dry Bulk sector in Singapore. The framework of the research is based on a comprehensive literature review of previous papers and supplemented with a survey questionnaire. Next, personal interviews were also conducted to match survey result with industrial implication. A gap analysis and mean score comparison were conducted to identify the issues, ranking and satisfaction of each service attributes in partnering relationship. The result of the project reveals that the service attributes with the largest gap in the Dry Bulk sector are: Accurate billing and documentation, Availability of equipment, Transit time, Willingness to meet service expectation and Claims handling and follow-up. Furthermore Shipper has ranked Service reliability and consistency, Freight rates, Willingness to meet service expectation, Availability of cargo space and Availability of equipment as the most critical factors in a partnership. The contribution of this project could be useful for Carrier to improve their performance and enhance their partnering relationship with the Shipper.